2020
DOI: 10.1093/biolinnean/blaa068
|View full text |Cite
|
Sign up to set email alerts
|

Population history of the golden eagle inferred from whole-genome sequencing of three of its subspecies

Abstract: Abstract The application of evolutionary genetic research to investigate the potential for endangered species to adapt to changing environments is important for conservation biology. Effective population size (Ne) is informative for understanding adaptive potential as it refers to the genetic variation in breeding individuals who have contributed to contemporary and historic population diversity. We reconstruct fluctuations in Ne in three golden eagle subspecies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…We hope and expect that these genomes will then be used by communities of evolutionary, ecological, conservation, and biotechnology scientists to carry out large-scale investigations of species and species groups, and we prioritize species for sequencing based on requests from these groups. From the genomes released already, we are aware of reuse by projects investigating population dynamics in threatened predator species (37), in fish stock monitoring, in lepidopteran speciation dynamics, in ancient environmental DNA analyses, and in large-scale phylogenetics. Additionally, we are developing a rich program of outreach and engagement work bringing DToL to and getting feedback from a wide diversity of stakeholders.…”
Section: Genome Assembly At Scalementioning
confidence: 99%
“…We hope and expect that these genomes will then be used by communities of evolutionary, ecological, conservation, and biotechnology scientists to carry out large-scale investigations of species and species groups, and we prioritize species for sequencing based on requests from these groups. From the genomes released already, we are aware of reuse by projects investigating population dynamics in threatened predator species (37), in fish stock monitoring, in lepidopteran speciation dynamics, in ancient environmental DNA analyses, and in large-scale phylogenetics. Additionally, we are developing a rich program of outreach and engagement work bringing DToL to and getting feedback from a wide diversity of stakeholders.…”
Section: Genome Assembly At Scalementioning
confidence: 99%
“…Sequences from a Spanish golden eagle (A. c. homeyeri; Alcaide et al, 2007; NCBI accession no. EF370905-EF370908) were used to perform a local BLAST search (BLAST+ version 2.5.0) against the Japanese and Scottish golden eagle genomes (Sato et al, 2020). Upon confirming homology, PCR amplification of the DRB exon 2 region with Acc2FC and Acc2RC was conducted in Japanese golden eagle samples.…”
Section: Mhc Analysismentioning
confidence: 99%
“…Compared with the vulnerable Galapagos Hawk, which has a similar population size (500-600 individuals, Bollmer et al, 2011), the Japanese golden eagle's diversity indices were significantly higher, suggesting that the Japanese golden eagle's MHC diversity is not critically low, despite their small population size and endangered status. A recent study suggested that Japanese golden eagles likely colonized Japan from both continental Asia and North America during the Last Glacial Period (Sato et al, 2020), which may have contributed to the diverse pool of MHC alleles. Moreover, given that the Japanese golden eagle population is small and isolated, there may be strong tendencies for MHC-based disassortative mating to avoid inbreeding (Potts et al, 1994;e.g., Ryukyu scops owl, Sawada et al, 2020).…”
Section: Mhc Diversitymentioning
confidence: 99%
“…The apparent declines, therefore, may not directly relate to immediate conservation problems, but fit within a longer-term pattern of abundance fluctuations. Therefore, there has been an increase in studies incorporating the perspective on longer-term changes in population sizes applied to conservation and management decision-making (Ardren and Kapuscinski, 2003;Brüniche-Olsen et al, 2018;Sato et al, 2020). Genetic techniques provide opportunities to understand historic context of temporal changes at much longer time scales.…”
Section: Rare and Declining Speciesmentioning
confidence: 99%
“…Genetic techniques provide opportunities to understand historic context of temporal changes at much longer time scales. Past population bottlenecks can be detected as well as precipitous declines hundreds and thousands of generations ago (Ramakrishan et al, 2005;Oldeschulte et al, 2017), and currently, assesments of single nucleotide polymorphisms (SNPs) across the entire genome allow exploration of these questions even when very few samples are available (Brüniche-Olsen et al, 2018;Sato et al, 2020). The gray whale (Eschrichtius robustus), for example, already lost its Northern Atlantic populations (probably due to environmental change and/or by commercial whaling), and it is now only found in the Northern Pacific Ocean (Alter et al, 2015).…”
Section: Rare and Declining Speciesmentioning
confidence: 99%